PENGARUH STUDENT TEAMS ACHIVEMENT DIVISION TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN PESERTA DIDIK KELAS V - Riyanti, Novi; Kartono, Kartono; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze how much influence cooperative learning models type student team achievement division on learning outcomes of Citizenship Education students of grade V students SDN 38 Pontianak Utara. The research method used is an experimental method with the form of Quasi Experimental Design and the type of nonequivalent control group design. The population is all V grade students of SDN 38 Pontianak Utara in 2017/2018 school year, amounting to 46 people, sampling is purposive sampling. The technique used in data collection is measurement with data collection tools used in the form of objective written tests. The results of the data analysis post-test average control class 68.25, while the average post-test experimental class 76.18. Based on the results of the data normality test using the Chi formula, the data squared is normally distributed. Then the data homogeneity test was performed with Fcount (1.12)> Ftable (1.92), declared homogeneous and followed by t-test with separated variance formula, obtained tcount (0.62)> t table (2.0168) with dk = 44, so Ha is accepted. From the results of the effect size calculation, ES is obtained for 0.83 with high criteria. So it can be concluded that learning by applying a cooperative model type student team achievement division provides a high influence on the learning outcomes of Civic Education students in grade V SDN 38 Pontianak Utara. Keywords: STAD, Learning Outcomes, Citizenship Education.